Oficina de brinquedos e brincadeiras na promoção de comportamentos sociais - Santos Soares, Leys Eduardo dos; Marin, Elizara Carolina; Gomes-da-Silva, Pierre Normando (2019)
This article presents the analysis of the results of an intervention with Toys and Games Workshop (OBBA by its acronym in Portuguese) on the behavior of children identified with antisocial conducts. Qualitative approach research, research-action type, was carried out with a group of the 5th year of elementary school, in a public school in João Pessoa-PB. The students were identified through an observation script and evaluated, before and during the workshop, by the Anti-Social Trend Scale (ETA by its acronym in Portuguese). After implementing the project over a period of time, in its different stages (Presentation, Evaluation, Implementation, and Intervention), a significant increase in social actions such as lending, offering, assisting, thanking, praising and dialoguing in those with antisocial behavior was evidenced.
Este artigo apresenta a análise dos resultados de uma intervenção com a Oficina de Brinquedos e Brincadeiras (OBBA) no comportamento de crianças identificadas com condutas antissociais. Pesquisa de abordagem qualitativa, do tipo pesquisa-ação, realizada com uma turma do 5º ano do Ensino Fundamental, numa escola pública de João Pessoa-PB. Os alunos foram identificados por meio de um roteiro de observação e avaliados, antes e durante a OBBA, pela Escala de Tendência Antissocial (ETA). Após período de implementação do projeto, em suas diferentes etapas (Apresentação, Avaliação, Implementação, Intervenção), evidenciou-se pela ETA um aumento significativo de ações sociais de emprestar, oferecer, auxiliar, agradecer, elogiar e dialogar, naqueles com condutas antissociais.
Keywords: Game; Teaching; Psychoanalysis; Physical Education; Jogo^lpt; Ensino; Psicanálise; Educação Física